THE CONCEPT OF “UZBEK PHILOSOPHY” AND ITS DISTINCTIVE FEATURES (International Congress on Economics, Management and Business Studies, 2026)
Throughout human history, we have often witnessed that when a nation’s statehood is stable and its spiritual potential is elevated, many areas, including its philosophy, develop rapidly. Conversely, during periods when statehood is lost or declines, national philosophy tends to stagnate or lose its significance. In this regard, the essence, manifestation, and stages of development of the concept of “Uzbek philosophy” cannot be fully understood separately from the history of our people, national statehood traditions, spiritual values, mentality, and worldview. Interpreting the concept in this way allows for the analysis of how the philosophy unique to our people emerges, evolves, and renews over time, i.e., how it moves from past to future as a socio-ethnic phenomenon, taking into account changes associated with the passage of time.